A comparative study of total quality management in healthcare from provider and patient perspectives at Al-Mouwasat University Hospital - Areej Eissa; Fatmah Al-Tarrab; Ezat Kasem; Yasser Al Zaim; Ali Hmidoush; Joudy Salloum; Jamal Ataya (Scientific Reports)
Abstract The Total Quality Management (TQM) is a strategic approach that aims to improve healthcare services by enhancing operational efficiency and ensuring patient satisfaction. Despite its widespread application in developed countries, TQM’s implementation in developing nations, particularly in the healthcare sector, has been limited. This study aims to evaluate TQM awareness, its application, and the effectiveness of scientific methods in improving healthcare services at Al-Mouwasat University Hospital, Syria. A cross-sectional, descriptive-analytical design was used, surveying 390 participants, including doctors, nurses, and patients. The study assessed TQM awareness, perceptions of hospital performance, and the use of scientific and statistical methods to enhance healthcare delivery. Statistical analyses, including the Mann–Whitney test, Kruskal–Wallis test, Dunn’s test, and Tukey test, were applied to identify significant differences in opinions across groups. The study found that doctors and nurses demonstrated neutral attitudes toward TQM principles, while patients showed higher satisfaction with healthcare services. Nurses were more supportive of scientific and statistical methods for improving hospital performance compared to doctors (P < 0.001). Significant differences were observed between doctors and nurses regarding patient interaction (P < 0.001), while no significant differences were observed regarding medical errors. Longer hospital stays correlated with higher patient satisfaction (P < 0.001), while no significant differences were found based on gender or age. These findings underscore the necessity of targeted training programs and organizational support to foster TQM adoption. By addressing systemic barriers, the hospital can enhance service delivery, ultimately contributing to better patient outcomes and sustained healthcare quality improvement.